Nitrate Accumulation and Expression Patterns of Genes Involved in Nitrate Transport and Assimilation in Spinach - Xiaoli Wang; Xiaofeng Cai; Chenxi Xu; Shui Wang; Shaojun Dai; Quanhua Wang (Molecules, 2018)
Excessive accumulation of nitrate in spinach is not only harmful to human beings, but also limits the efficiency of nitrogen usage. However, the underlying mechanism of nitrate accumulation in plants remains unclear. This study analyzed the physiological and molecular characteristics of nitrate uptake and assimilation in the spinach varieties with high or low nitrate accumulation. Our results showed that the variety of spinach with a high nitrate content (So18) had higher nitrate uptake compared to the variety with a low nitrate content (So10). However, the nitrate reductase activities of both varieties were similar, which suggests that the differential capacity to uptake and transport nitrate may account for the differences in nitrate accumulation. The quantitative PCR analysis showed that there was a higher level of expression of spinach nitrate transporter (SoNRT) genes in So18 compared to those in So10. Based on the function of Arabidopsis homologs AtNRTs, the role of spinach SoNRTs in nitrate accumulation is discussed. It is concluded that further work focusing on the expression of SoNRTs (especially for SoNRT1.4, SoNRT1.5 and SoNRT1.3) may help us to elucidate the molecular mechanism of nitrate accumulation in spinach.